PENGARUH UMUR PERUSAHAAN, OPINI AUDIT, DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Aneka Industri Tahun 2021-2023): PENGARUH UMUR PERUSAHAAN, OPINI AUDIT, DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Aneka Industri Tahun 2021-2023) - Widia, Patma; Wulandari, Ika (ITB AAS Indonesia Surakarta, 2025)
This study was conducted to determine and analyze the effect of company age, audit opinion, and company size on audit delay (an empirical study of manufacturing companies in the miscellaneous industry sub-sector from 2021 to 2023). The population of this study was all manufacturing companies in the miscellaneous industry sub-sector listed on the Indonesia Stock Exchange (IDX). The sampling technique used in this study was purposive sampling. Data analysis used the SPSS application. The results of this study indicate that company age partially significantly influences audit delay in manufacturing companies in the miscellaneous industry sub-sector listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The results of this study indicate that audit opinion partially does not significantly influence audit delay in manufacturing companies in the miscellaneous industry sub-sector listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The results of this study indicate that company size partially significantly influences audit delay in manufacturing companies in the miscellaneous industry sub-sector listed on the Indonesia Stock Exchange (IDX) in 2021-2023.